A Cooperative Computer Game for Public Efficiency Development (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
This paper presents a design case study of SIDES: Design Interfaces to Develop Effective Public Efficiency. SIDES is a tool designed to help adolescents in Public group therapy, specifically individuals with Asperser’s Syndrome, practice effective group work efficiency using a four-player cooperative computer game that runs on computer games technology. We are represent the design process and evaluation of SIDES conducted over a period of six months with a middle school Public group therapy class. Our findings indicate that computer games are a motivating and supported tool for effective group work among. My target population and reveal different design lessons to inform the development of similar systems.